Detection of inducible clindamycin resistance in Staphylococcus aureus from various samples in a tertiary care hospital - Kumar, Rohit; ., Jagarti; Sarma, Mrinmoy; Shalini, Gautam (International Journal of Research in Medical Sciences, 2019)
Background: The increasing frequency of MRSA infections and rapidly changing patterns in antimicrobial resistance, led to renewed interest in the usage of Macrolides-Lincosamide-Streptogramin B (MLSB) antibiotics to treat Staphylococcus aureus infection. Clindamycin is an important drug used in the treatment of MRSA and MSSA infection. The aim of this study was to determine inducible and constitutive clindamycin resistance among clinical isolates of Staphylococcus aureus by D-test. Methods: During a period of 6 months from July 2018 to December 2018, a total of 100 Staphylococcus aureus isolated from different clinical samples were subjected to routine antibiotic sensitivity testing by Kirby Bauer’s disc diffusion method. Methicillin-resistance was determined by using the cefoxitin (30 µg) disc. Incidence of MLSBc and MLSBi in Staphylococcus aureus isolates by D-test as per CLSI guidelines. Results: Out of 100 isolates of Staphylococcus aureus obtained from 350 clinical samples, 70(70%) were found to be MRSA and 30(30%) were MSSA. Among 100 Staphylococcus aureus isolates, 40% isolates showed MLSBi resistance, 28% isolates showed MLSBc resistance, 6% isolates showed MS phenotype and 26% isolates showed Sensitive phenotype. MLSBc and MLSBi were found to be higher in MRSA as compared to MSSA (21%, 27% and 7%, 10% respectively). All clinical isolates showed 100% sensitivity to Vancomycin and Linezolid in routine antibiotic susceptibility testing. Conclusions: Continuous surveillance of the MLSB resistance is important and required before the prescription of clindamycin to treat MRSA infections.